Dampak Kebijakan Penerimaan Guru Pegawai Pemerintah dengan Perjanjian Kerja terhadap Lembaga Pendidikan Swasta - Irnie Victorynie; Umdatul Mursiyah; Siti Apipah Zachroh (CV. Creative Tugu Pena, 2024)
In order to improve the quality of education and SDM (Human Resource) in Indonesia, the government is trying to take a policy in the hope of the exhaustion in the field of teaching both for the quality knowledge and skills of students and career development of teachers. As for the policy based on the Law No. 5 of 2014 on State Civil Appliances, there are only two types of ASN officials: Civil State Officials (PNS) and Government Officers with employment agreements. (PPPK). But on the other hand, this policy has become a new controversy in the world of education, especially for private institutions. As far as this research is concerned, it uses a qualitative approach using case studies as well as interviews. Thematic analysis is used to analyze data; after that, data from the interview is copied into writing and keywords are identified for further analysis. The researchers also found themes for further exploration. The results of this study show that this policy, rather than providing solutions, presents new polemics in the world of education.